Causal influences of osteoarthritis on COVID-19: a Mendelian randomization study - Fu, Li; Baranova, Ancha; Cao, Hongbao; Zhang, Fuquan (Frontiers in Medicine, 2023)
Objective: Although observational and genetic studies have indicated a correlation between OA and COVID-19, it remains uncertain whether osteoarthritis (OA) contributes to the severity of COVID-19. Here, we aimed to investigate the potential causal links between the two. Methods: In this study, we conducted Mendelian randomization (MR) analysis to investigate whether there is a potential causal connection between OA and COVID-19 outcomes. The analysis utilized publicly available GWAS summary datasets, incorporating data on OA (N = 455,221), SARS-CoV-2 infection (N = 2,597,856), hospitalized COVID-19 (N = 2,095,324), and critical COVID-19 (N = 1,086,211). Additionally, we performed a literature analysis to establish a molecular network connecting OA and COVID-19.The MR analysis showed causal effects of OA on hospitalized